Fractures on the chest radiograph in detection of alcoholic liver disease. Issue 6342 (28th August 1982) - Lindsell, D R; Wilson, A G; Maxwell, J D
Abstract : The presence of fractures seen on routine chest radiography was assessed in patients with liver disease to see whether it might provide a useful marker of alcoholism. Chest radiographs taken at the time of liver biopsy were examined in 149 patients–72 with alcoholic liver disease (32 (44%) cirrhotic) and 77 with various forms of non-alcoholic liver disease (15 (19 . 5%) cirrhotic)–and in 149 controls. Fractures (85 rib, two clavicular) were much more common in patients with alcoholic liver disease (20 subjects; 28%) than in patients with non-alcoholic liver disease (1; 1 . 3%) or controls 10; 6 . 7%). In alcoholic liver disease rib fractures were significantly more likely to be bilateral or multiple (more than two) or both (p less than 0 . 01). Of patients with alcoholic liver disease, those with fractures were significantly older than those without, but there was no difference in sex, social class, the proportion with cirrhosis, or the proportion known to be alcoholic at the time of the radiograph. In liver disease fractures on the chest radiograph diagnosed alcoholism with 95% specificity and 28% sensitivity. These often overlooked or ignored findings in the chest radiograph may have a wider role in the detection of alcoholism.